Interprofessional Education Using a Palliative Care Simulation. Issue 3 (May 2016) - Saylor, Jennifer; Vernoony, Stephanie; Selekman, Janice; Cowperthwait, Amy
Abstract : This quasi-experimental pretest-posttest study measured self-efficacy, attitudes toward physician-nurse collaboration, and interprofessional competencies as outcomes of a palliative care simulation. Based on experience level, teams of participants, 1 consisting of nursing/medical students and the other of nursing/medical health care professionals, completed a palliative care simulation as part of their education. Self-efficacy and attitudes toward physician-nurse collaboration were measured before and after simulation. Interprofessional competency was measured during the simulation. The results revealed a significant improvement in the previously mentioned measures, and interprofessional competency scores varied by profession and evaluator.